2012
DOI: 10.1145/2362364.2362370
|View full text |Cite
|
Sign up to set email alerts
|

The impact of interface affordances on human ideation, problem solving, and inferential reasoning

Abstract: This article presents two studies investigating how computer interface affordances influence basic cognition, including ideational fluency, problem solving, and inferential reasoning. In one study comparing interfaces with different input capabilities, students expressed 56% more nonlinguistic representations (diagrams, symbols, numbers) when using pen interfaces. A linear regression confirmed that nonlinguistic communication directly mediated a substantial increase (38.5%) in students' ability to produce appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 21 publications
(31 reference statements)
2
26
0
1
Order By: Relevance
“…The present findings are consistent with other recent work showing that students' inferential accuracy was significantly better when using a digital pen and paper interface, compared with nondigital pen and paper tools [10]. This work also demonstrated that students' improved inferential reasoning when using the pen interface was mediated by a higher rate of diagramming and more accurate diagrams, which were visually available to inspect and led to more accurate scoping of conclusions [10].…”
Section: Can Computer Input Capabilities Influence the Accuracy Of Husupporting
confidence: 91%
See 2 more Smart Citations
“…The present findings are consistent with other recent work showing that students' inferential accuracy was significantly better when using a digital pen and paper interface, compared with nondigital pen and paper tools [10]. This work also demonstrated that students' improved inferential reasoning when using the pen interface was mediated by a higher rate of diagramming and more accurate diagrams, which were visually available to inspect and led to more accurate scoping of conclusions [10].…”
Section: Can Computer Input Capabilities Influence the Accuracy Of Husupporting
confidence: 91%
“…This work also demonstrated that students' improved inferential reasoning when using the pen interface was mediated by a higher rate of diagramming and more accurate diagrams, which were visually available to inspect and led to more accurate scoping of conclusions [10].…”
Section: Can Computer Input Capabilities Influence the Accuracy Of Humentioning
confidence: 76%
See 1 more Smart Citation
“…Oviatt et al [22] suggest that using paper stimulates ideation, and is particularly effective in supporting nonlinguistic or spatial representations that are poorly supported by traditional interfaces. Contemporary composers use paper not only to express musical ideas but also to explore and complete the detailed implementation of their final musical score [13,26].…”
Section: Pen-based Interfaces and Creative Workmentioning
confidence: 99%
“…Others involve field studies with open-ended explorations of interactive tools [11,22]. Still others propose new metrics, such as degrees of freedom for musical control or required expertise [5].…”
Section: Evaluating Composition Support Toolsmentioning
confidence: 99%